2017
DOI: 10.3892/or.2017.5365
|View full text |Cite
|
Sign up to set email alerts
|

Core-shell lipid polymer nanoparticles for combined chemo and gene therapy of childhood head and neck cancers

Abstract: Pediatric head and neck cancers account for overall 12% of all pediatric cancers. Despite recent advances in therapeutic modalities, children with tumor metastasis have poor prognosis. Therefore, there is an unmet need for new and effective treatment modalities for pediatric head and neck cancers. The present study describes a simple and efficient method for fabrication of cationic lipid‑polymer hybrid nanoparticles (CLPNs) for co‑delivery of cisplatin (CDDP) and DNA (CDDP/DNA CLPNs) for the therapy of childho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
1
7
1
Order By: Relevance
“…Hence the cytotoxic effect of cisplatin is time and concentration dependent. Optimum activity after 48 hours is in agreement with the previous studies (Zhang et al., 2017). It is also important that after 48 hours, the cisplatin loaded lipid-polymer hybrid nanoparticles showed a 20–30% increased cytotoxicity at same concentration as compared to 24 hours and up to 50% of cell death at the lowest concentration.…”
Section: Resultssupporting
confidence: 93%
“…Hence the cytotoxic effect of cisplatin is time and concentration dependent. Optimum activity after 48 hours is in agreement with the previous studies (Zhang et al., 2017). It is also important that after 48 hours, the cisplatin loaded lipid-polymer hybrid nanoparticles showed a 20–30% increased cytotoxicity at same concentration as compared to 24 hours and up to 50% of cell death at the lowest concentration.…”
Section: Resultssupporting
confidence: 93%
“…One of the major concerns for nanoparticles is the electrostatic interaction between the vectors and the plasma composition such as proteins, which will increase the size of the nanoparticles. 51 During the stability studies, there were no remarkable changes in the particle size in the presence of plasma and during 3 months of storage at 4°C, which would prove the ability of the system when administration in vivo and enhance the targeting proportion of the vector to the target organ, and thus would be favorable to improve the therapeutic effects.…”
Section: Discussionmentioning
confidence: 90%
“…The presence of such a number of duplicating mechanisms suggests that the cell perceives 8-oxoguanine as an extremely serious threat that must be quickly eliminated [55]. Studies (Figure 5b) show that borosiloxane did not affect the formation of 8-oxoguanine in DNA in vitro, which significantly distinguishes it from other materials [56][57][58]. It was shown that when zinc oxide nanoparticles appear in BS, the rate of 8-oxoguanine formation in DNA significantly increases.…”
Section: Discussionmentioning
confidence: 98%